Mortality of Laying Hens in Two Municipalities of Camagüey during the 2011-2015 Period - Liliana Soris Saavedra; Francisco González Aguilar; Sahirys Casas Rodríguez; Neftaly Haymar Cervantes; Dailenys Batista Hernández (Agrisost, 2018)
This research took place at the National Poultry Company (UECAN), in Camagüey. The aim of the study was to assess the mortality causes in three layer farms of the company in the municipalities of Camagüey and Minas, in the 2011-2015 period. The mortality control records were reviewed. The items checked corresponded to number of deaths, causes, etiology-related, and year. The death causes were pooled depending on the diseases (colibacillosis, salmonellosis, infectious coryza, mycoplasmosis, and coccidiosis); the noxae caused by undernourishment, animals eaten by rats, accidents, prolapse, cannibalism, and pecking were also among the causes of deaths by mismanagement. It was concluded that the causes of mortality due to mismanagement, prolapse, cannibalism, and pecking, were the highest. The diseases represented the highest noxae causes. The differences between the causes of disease-related deaths and the evidence of mismanagement in the province were striking. The municipality of Camagüey showed higher mortality rates than Minas.